2012
DOI: 10.1366/12-06617
|View full text |Cite
|
Sign up to set email alerts
|

Single-Pulse Standoff Raman Detection of Chemicals from 120 m Distance during Daytime

Abstract: The capability to analyze and detect the composition of distant samples (minerals, organics, and chemicals) in real time is of interest for various fields including detecting explosives, geological surveying, and pollution mapping. For the past 10 years, the University of Hawaii has been developing standoff Raman systems suitable for measuring Raman spectra of various chemicals in daytime or nighttime. In this article we present standoff Raman spectra of various minerals and chemicals obtained from a distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 48 publications
1
55
0
3
Order By: Relevance
“…Misra et al demonstrated that visible Raman spectra can be measured from greater than 100 m standoff distances . Single 100 mJ pulses of 532 nm light‐excited NB, potassium perchlorate, and NH 4 NO 3 samples inside sealed glass vials 120 m away (Fig.…”
Section: Standoff Explosive Detectionmentioning
confidence: 99%
“…Misra et al demonstrated that visible Raman spectra can be measured from greater than 100 m standoff distances . Single 100 mJ pulses of 532 nm light‐excited NB, potassium perchlorate, and NH 4 NO 3 samples inside sealed glass vials 120 m away (Fig.…”
Section: Standoff Explosive Detectionmentioning
confidence: 99%
“…These are essentially the same instrumental requirements as those of LIBS, and both are often used together [118][119][120][121]. Very good signal-to-noise has been obtained for bulk explosive materials (tens of gram quantities) in single-shot [122] and multiple-pulse [123] spectra measured beyond 100 m in daylight conditions, and at 470 m for multiple-pulse measurement (1-10 s) during heavy rainfall [124,125].…”
Section: Ramanmentioning
confidence: 99%
“…Because all elements emit light of characteristic frequencies when excited to sufficiently high temperatures, LIBS can (in principle) detect all elements, limited only by the power of the laser as well as the sensitivity and wavelength range of the spectrograph & detector (Pasquini et al, 2007). Stand-off or remote LIBS is able to excite plasma and retrieve information from plasma at long distance from the samples (Misra et al, 2012;Zachhuber et al, 2011). The apparatus coupled with appropriate excitation laser source and telescope system has been reported to detect samples more than 50 m away.…”
Section: Introductionmentioning
confidence: 99%